LUMBAR SYMPATHECTOMY IN OLDER PATIENTS - Movius, Herbert J. (1954)
Of 43 older patients (aged 65 to 83 years) with arteriosclerosis obliterans treated by lumbar sympathectomy for one or both limbs, 19 had excellent result, 13 had fair result and four had poor result. One died postoperatively and six later. Results were better than prognosticated from response to sympathetic block. Thirty-four patients considered the operation worth while and twelve, after unilateral sympathectomy, requested operation for the other limb also. Twenty-four after operation could walk farther without claudication.